The Prenatal Primary Nursing Care Experience of Pregnant Women in Contexts of Vulnerability: A Systematic Review With Thematic Synthesis. (8th July 2022) - Hudon, Émilie; Hudon, Catherine; Chouinard, Maud-Christine; Lafontaine, Sarah; de Jordy, Louise Catherine; Ellefsen, Édith
Abstract : The contexts of vulnerability are diversified and cover a wide range of situations where pregnant women are likely to experience threats or disparities. Nurses should consider the particular circumstances of women in contexts of vulnerability. We used a qualitative thematic synthesis to describe the experience of these women regarding their prenatal primary nursing care. We identified that the women's experience is shaped by the prenatal care. The fulfillment of their needs and expectations will guide their decision regarding the utilization of their prenatal care. We propose a theoretical model to guide nurses, promoting person-centered delivery of prenatal care.